Exploring Dialogic Feedback Practices in English Writing for Academic Purposes - Alda Fitrianingsih; Sri Lestari (Jurnal Lingua Idea, 2025)
Dialogic feedback has been widely discussed in EFL contexts, limited research has examined its practical implementation and students’ perceptions in undergraduate academic writing classes in Indonesian higher education. Therefore, this study aims to address this gap by providing empirical evidence from a regular classroom setting. Using a qualitative case study design, data were collected through classroom observations, semi-structured interviews with one lecturer and ten students, and document analysis. The participants were selected through purposive sampling from an undergraduate English Education program to ensure relevance to the research focus. Data were analyzed using thematic analysis following Braun and Clarke’s framework to identify patterns across observation, interview, and document data. The implementation followed Er’s (2020) three-phase framework: preparation, implementation, and follow-up. The study revealed that in the preparation phase, the teacher selected tasks aligned with learning goals and fostered an open classroom atmosphere. The implementation phase involved interactive discussions and open-ended questioning to encourage reflection and self-revision. The follow-up phase focused on monitoring students’ revisions and providing additional clarification. Findings also indicate that students generally perceived dialogic feedback as supportive, interactive, and beneficial for improving writing skills, though some reported feelings of stress or anxiety. The study concludes that dialogic feedback enhances motivation, critical thinking, and academic writing quality, but requires active student engagement and consistent teacher facilitation.